Prevalence of HBsAg positive among non- immunized junior high school students in Bandung - Lia Marlia K.; Yasmar Alfa; Iesje Martiza; Dwi Prasetyo (Paediatrica Indonesiana, 2007)
Background Sero-epidemiologic survey of hepatitis B is used todetermine the prevalence of hepatitis B infection in community,particularly among population which has not been covered byhepatitis B immunization program.Objective To determine the prevalence of HBsAg positive amongjunior high school’s students in Bandung.Methods A cross-sectional study was conducted on junior high school(SMP) students. Subjects were selected randomly using stratifiedcluster sampling of 4 junior high schools in Bandung. The inclusioncriteria were students of first and second grade, lived in Bandungarea, without history of hepatitis B immunization. Subjects wereinterviewed and were screened for HBsAg using Reverse PassiveHemagglutination technique.Results There were 341 subjects consisted of 201 girls and 140boys. None of the subjects had any sexual intercourse or intravenousdrugs, while 261 subjects (76.5%) had shared personal care. Historyof blood transfusion was found in 13 subjects (3.8%), tattooing in2 (3.8%), body piercing in 28 (8.2%), and contact with chronicliver disease patients in 16 (4.7%). Based on HBsAg serologic test,3 subjects (2 boys and 1 girl) were found to be positive, thus HBsAgpositive prevalence was 0.9% (95%CI -0.001;0.019). Two of themhad shared personal care with their relatives or friends. None ofthem had tattoo, body pierce, blood transfusion, or contact withchronic liver disease patients. Their physical condition were withinnormal limit. One of them refused to do further laboratory testsbecause no permission from his parents. Liver function of thosestudents were normal, anti-HBc IgM were negative, and total anti-HBc were positive in two of them.Conclusion The prevalence of HBsAg positive in junior highschool students in Bandung is low and there is no obvious riskfactor for the transmission of the disease.